Proposal of lines of research for the Faculty of Chemical Engineering of the National University of Trujillo using Power bi (SCIÉNDO INGENIUM, 2021)
Research, in its broadest sense, not only refers to the generation of knowledge but also to the transfer of technologies or patents that solve problems in society. For its fulfillment, a methodology and updating of the research lines for the Faculty of Chemical Engineering is imperative. In this research, as a starting point, 161 undergraduate theses developed between the schools of Chemical Engineering and Environmental Engineering were evaluated. To define the lines, the scheme of Resolution RCU 209-2019 / UNT and the guide of the Organization for Economic Cooperation and Development (OECD) recommended by Concytec were used. Data analysis generally requires powerful, agile and dynamic software. The chosen software was Power bi through which graphs of the circular type and stacked bars were made. To complement the lines, it is joining the areas of Industrial Biotechnology and Environmental Biotechnology as they are closely related to chemical and environmental processes. It is emphasized that for the updating of the lines, the opinion of the faculty teachers and publications of scientific research is also required.
Keywords: Power bi; investigation; chemical engineering